ANALISIS PEMIKIRAN SULAIMAN AL-ASYQAR TENTANG SIFAT ALLAH DALAM KITAB ZUBDAH AT-TAFSIR - Rizal Samsul Mutaqin; Siti Urbah Ashiroh (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2021)
This study aims to find understanding and thought Sulaiman Al-Asyqar behind the interpretation of the verses of the nature of Allah 20 in the kitab Zubdah At-Tafsir. Sulaiman Al-Asyqar is a great scholar and as one of the prophet’s sunnah flags one of them’s a dark thought. Zubdah At-Tafsir is one of the kitab interpretation who used of interpretation Riwayah and Dirayah. This interpretation was also mentioned taking on kalam features Ahlu Sunnah. Research methods that could facilitate conducting this analysis are qualitative research methods. This research data-retrieval technique uses observation and documentation, the point of observation and documentation here is kitab Zubdah At-Tafsir. As for this research data analysis technique using text maudhu’i (thematic) which deals with the Al-Quran according to a fixed theme or title. The result research shows that: (1) Sulaiman Al-Asyqar in interpreting verses of the nature of Allah 20 using the interpretation method ijmali (global) and and use features i’tiqady (theology). (2) Understanding and thinking Sulaiman Al-Asyqar the interpretation of passages in Allah 20 nature differs from streams of islamic theology adjoining: Asy’ariyah, Mu’tazilah, and Maturidiyah. (3) Sulaiman Al-Asyqar in interpreting verses of the nature of Allah 20 using insight and thinking that tend to lead to Ahlu Sunnah Wa Al-Jama’ah.